Ischemic and bleeding outcomes after coronary artery bypass grafting among patients initially treated with a P2Y12 receptor antagonist for acute coronary syndromes: Insights on timing of discontinuation of ticagrelor and clopidogrel prior to surgery. Issue 6 (September 2019) - Russo, Juan J; James, Tyler E; Ruel, Marc; Dupuis, Jean-Yves; Singh, Kuljit; Goubran, Daniel; Malhotra, Nikita; Rubens, Fraser; Chong, Aun-Yeong; Hibbert, Benjamin; Boland, Paul; Tran, Diem TT; et al.
Background: Clinical outcomes in acute coronary syndrome patients treated with P2Y12 inhibitors who require urgent coronary artery bypass grafting (CABG) have not been well studied. Methods: We examined clinical outcomes in acute coronary syndrome patients in relation to the timing of CABG following P2Y12 inhibitor discontinuation (<72 h, 72 h to five days, >5 days). The primary ischemic outcome was a composite of death, reinfarction, need for revascularization, or stroke. The primary safety outcome was bleeding of at least moderate severity as defined by a Universal Definition of Perioperative Bleeding class ≥2. Results: Among 508 patients (95 ticagrelor, 413 clopidogrel), the timing of CABG following P2Y12 inhibitor discontinuation was <72 h in 32.1%, 72 h to five days in 23.2% and >5 days in 44.7%. Compared with CABG within 72 h, CABG 72 h to five days (adjusted odds ratio (OR) 0.35; 95% confidence interval (CI) 0.14–0.85; p =0.02) but not >5 days (adjusted OR 0.62; 95% CI 0.33–1.16; p =0.14) after P2Y12 inhibitor discontinuation was associated with lower odds of the primary ischemic outcome. Compared with CABG within 72 h, CABG 72 h to five days (adjusted OR 0.38; 95% CI 0.22–0.66; p =0.001) and >5 days (adjusted OR 0.33; 95% CI 0.20–0.53; p <0.001) after P2Y12 inhibitor discontinuation were associated with lower rates of Universal Definition of Perioperative Bleeding class ≥2 bleeding. Conclusions: CABG within 72 h after P2Y12 inhibitor discontinuation is associated with excess ischemia and bleeding. The rates of ischemic and bleeding events were comparable in patients undergoing CABG 72 h to five days compared with >5 days after P2Y12 inhibitor discontinuation.